Metabolic syndrome in relation to Barrett's esophagus and esophageal adenocarcinoma: Results from a large population-based case-control study in the Clinical Practice Research Datalink. (June 2016) - Drahos, Jennifer; Li, Lin; Jick, Susan S.; Cook, Michael B.
Highlights: Metabolic syndrome (MetS) increased risk of Barrett's esophagus (BE). GERD modified the association with increased risk confined to those without reflux. No association between MetS and risk of EA was detected. MetS may represent a reflux-independent inflammatory pathway that increases BE risk. Abstract: Gastroesophageal reflux disease (GERD) causes local chronic inflammation that increases risks of Barrett's esophagus (BE) and esophageal adenocarcinoma (EA), yet symptomatic GERD is absent in approximately half of all such patients. Obesity exacerbates GERD and is also a component of metabolic syndrome (MetS). We evaluated the hypothesis that MetS is a GERD-independent mechanism by which obesity is associated with increased risks of BE and EA using data from the UK Clinical Practice Research Datalink. BE cases ( n = 10, 215) and EA cases ( n = 592) were each individually matched to five population controls based on age, sex, and general practice. MetS was defined as occurrence of at least three of the following: obesity, type 2 diabetes, hypertension, and high cholesterol. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using conditional logistic regression. MetS was marginally associated with BE (OR = 1.12, 95%CI 1.00–1.25). Similar effects were found for the individual component factors of obesity, hypertension, and high cholesterol. History of GERD modified the association (P -effect modification <1E–5), with the MetS-BE association confined to patients without a history of GERD (OR = 1.33, 95%CI 1.12–1.58). No association between MetS and risk of EA was detected in the main or stratified analyses. In this large population-based case-control study, individuals with MetS had a marginally increased risk of BE in the absence of GERD. The systemic inflammatory state (MetS) may represent a reflux-independent inflammatory pathway that increases the risk of BE. MetS did not increase risk of EA in this study population.